The relationship between the level of knowledge and attitudes with the behavior of pregnant women in recognizing the danger signs of pregnancy in the city of Padang in 2021 - Kurniawan, Deden; Ferry, Ferdinal; Basyir, vaulinne (Fakultas Kedokteran Universitas Andalas, 2022)
Introduction: Lack of knowledge of mothers in recognizing danger signs during pregnancy is one of the factors for the high maternal mortality rate. This study aims to determine the relationship between the level of knowledge and attitudes with the behavior of pregnant women in recognizing the danger signs of pregnancy in the city of Padang. Methods: This research using a cross sectional approach to 56 pregnant women at 3 Public Health Centers in Padang City from January 2022 to April 2022. To determine that relation, the chi-square test was used with 95% CI (Î± 0.05). Results: The results shows that most of the respondents who use the KIA book have a good knowledge (83%), have a positive attitude (89.3%) and behave appropriately (89.3%) and there is also a relationship between the level of knowledge and behavior. KIA book users in recognizing the danger signs of pregnancy (P = 0.04) and the relationship between attitudes and behavior of pregnant women using KIA books in recognizing pregnancy danger signs (p = 0.001). The relationship between knowledge and attitudes with the behavior of KIA book users in recognizing the danger signs of pregnancy(p-value0.001versus0.846). Conclusion: There is a relation between the level of knowledge and the behavior of KIA book users in recognizing the danger signs of pregnancy, between attitudes and the behavior of pregnant women using KIA books in recognizing the danger signs of pregnancy and attitudes have a more dominant influence than knowledge.